1977
DOI: 10.1111/j.1440-6055.1977.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sensory Nervous System of the Adult Cattle Tick Boophilus Microplus (Canestrini) Ixodidae Part Ii. Scanning Electron Microscopy

Abstract: The morphology of the sensory receptors on tarsus I and on the mouthparts of the cattle tick Boophiitis ~~i c r o p h r s were examined by means of scanning electron microscopy. Features not resolved by light microscopy were revealed. The number of seiisilla and their morphology are unique to B. tnicrophrs though similar to those of other tick species already described. The sensory setae found include mechanoreceptors, contact and olfactory chemoreceptors. Of s p e c~l interest, on each inner cheliceral digit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…These 4 compounds evoked SSR responses to 3 different ORNs on DIII.2. These results agree with previous studies that reported that DIII.2 is innervated by 4-5 neurons (Waladde 1976), although one of them is a thermoreceptor (Waladde 1987). The sensillum chaeticum DV.2 of R. sanguineus s.l females possibly has 2 ORNs that were stimulated by isovaleric acid, hexanal, and schnauzer extract.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These 4 compounds evoked SSR responses to 3 different ORNs on DIII.2. These results agree with previous studies that reported that DIII.2 is innervated by 4-5 neurons (Waladde 1976), although one of them is a thermoreceptor (Waladde 1987). The sensillum chaeticum DV.2 of R. sanguineus s.l females possibly has 2 ORNs that were stimulated by isovaleric acid, hexanal, and schnauzer extract.…”
Section: Discussionsupporting
confidence: 92%
“…The sensillum chaeticum DV.2 of R. sanguineus s.l females possibly has 2 ORNs that were stimulated by isovaleric acid, hexanal, and schnauzer extract. Morphologically, DV.2 contains more than 2 ORNs per sensillum in Rhipicephalus (Boophilus) microplus (Canestrini) adults (Waladde 1976), while the DV.2 of A. americanum may contain 3-4 ORNs of unknown physiological function (Foelix andAxtel 1971, Waladde 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary morphological studies, using light microscopy and scanning electronmicroscopy, have shown that the chelicerae of B. microplus closely resemble those described from other tick species (Arthur 1946(Arthur , 1951 ; Gregson 1960) apart from the presence of previously undescribed structures resembling sensilla (Waladde 1976(Waladde , 1977. This paper describes the results of transmission electronmicroscopical and electrophysiological studies of the newly found cheliceral sense organs.…”
Section: Introductionmentioning
confidence: 65%
“…Although the cheliceral papilla was considered previously to be a putative chemoreceptor (Waladde 1976(Waladde , 1977, ultrastructural results have caused this opinion to be revised. Figs 6-8 show that its central depression is not a pore containing dendrites and Fig.…”
Section: Results and Conclusion Ultrastriicturementioning
confidence: 99%
“…Haller’s organ has been suggested to play a role in the perception of other stimuli as well, e.g., infrared light ( Mitchell et al., 2017 ). Ticks can respond to the environment also due to numerous sensory bristles in the body and on the legs, which detect olfactory and thermal stimuli as well as the level of air humidity ( Lees, 1969 ; Waladde, 1977 ). The sense organs include also the so-called areae porosae , a pair of depressions at the base of the head in female Ixodidae ticks ( Woolley, 1972 ; Hess and Vlimant, 1986 ).…”
Section: Possible Stronger Attraction To Ticks After Alcohol Consumptionmentioning
confidence: 99%